2003
DOI: 10.1128/aem.69.7.4159-4166.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Dehalogenation of Brominated Phenolic Compounds by Microorganisms Associated with the Marine Sponge Aplysina aerophoba

Abstract: Marine sponges are natural sources of brominated organic compounds, including bromoindoles, bromophenols, and bromopyrroles, that may comprise up to 12% of the sponge dry weight. Aplysina aerophoba sponges harbor large numbers of bacteria that can amount to 40% of the biomass of the animal. We postulated that there might be mechanisms for microbially mediated degradation of these halogenated chemicals within the sponges. The capability of anaerobic microorganisms associated with the marine sponge to transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
89
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 44 publications
2
89
0
2
Order By: Relevance
“…We have previously demonstrated that the sponge Aplysina (synonym Verongia) aerophoba, which produces a brominated tyrosine derivative, harbours anaerobic, reductively dehalogenating bacteria (Ahn et al, 2003). From Aplysina sponge material, we maintained stable anaerobic enrichment cultures by using lactate as an electron donor and bromophenols as electron acceptors.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that the sponge Aplysina (synonym Verongia) aerophoba, which produces a brominated tyrosine derivative, harbours anaerobic, reductively dehalogenating bacteria (Ahn et al, 2003). From Aplysina sponge material, we maintained stable anaerobic enrichment cultures by using lactate as an electron donor and bromophenols as electron acceptors.…”
mentioning
confidence: 99%
“…These compounds may serve as a chemical defence against predators and may inhibit biofouling (Weiss et al, 1996). In addition, Aplysina sponges harbour large amounts of bacteria, which can amount to 40 % of the biomass of the animal, and it has been hypothesized that some of the organobromine compounds may in fact be synthesized by bacteria associated with the sponge (Hentschel et al, 2001(Hentschel et al, , 2003.As the marine environment is a particularly rich source of biogenic organohalides, it is not surprising that dehalogenating bacteria have been isolated from marine environments. Two dehalogenating bacteria in the genus Abbreviations: 2BP, 2-bromophenol; APS, adenosine 59-phosphosulfate; DGGE, denaturing gradient gel electrophoresis; TRF, terminal restriction fragment; T-RFLP, terminal restriction fragment length polymorphism.…”
mentioning
confidence: 99%
See 3 more Smart Citations